The Values of Islamic Education in Surah Al-Jumu’ah verses 1 – 5 (Comparative study between Tafsir Al-Maraghi and Tafsir Ibn Katsir) - Saiful Anwar; Aunul Izzah Mahmudah (Educan : Jurnal Pendidikan Islam, 2021)
.The background to this research is that education in Islam is currently experiencing the crisis of Islamic values that led to the decline. The observers for education analysed several causes of decline, including life materials that did not refer to its main source, the occurrence of social and cultural crises, the loss of good will and the right faith. In the face of these problems, we must return to the Koran. The concepts presented by the Koran are always linked to the problems faced by human beings.This research is a library research. This research uses the comparative descriptive approach with the qualitative method. The data collection method used by the researcher is authentication techniques. The data collected by the researcher are Tafsir al-Maraghi, Tafsir Ibn Katsir, and books and magazines related to the address the researcher is studying. After the data is collected, the data is sorted according to the research needs. Then analyzing the data using the analytical method and the comparative method, then conclusions about the values of Islamic education in Surat Al-Jumah Verse 1-5.The results of this research indicate that 1) for the tafsir al-Maraghi there are three values of Islamic education mentioned in Surah Al-Jumah verse 1-5, meaning belief education about belief in God, the Lord of the two sciences, belief in his names and attributes, his book which revealed to his Messenger, and faith in his messengers, education of worship means remembrance To God always alone, and moral upbringing to imitate the commendable qualities and attitudes of the Prophet Muhammad, may God’s prayers and peace be upon him, which must be applied to restore the values of Islamic education that live in the crisis of decline. 2) According to Ibn Katsir’s interpretation, there are the values of Islamic education in Surat Al-Jumu’ah verse 1-5 which means belief education about belief in God, the Lord of the two knowledge, belief in his names and attributes, and his books which revealed to his Messenger, and faith in his messengers, education of worship means remembrance to God alone always, and moral education to imitate attributes And the praiseworthy positions of the Prophet Muhammad, may God bless him and grant him peace, which considers these three values an important basis in Islam. In general, these two explanations have some similarities. 3) It is the interpretation of the verse by the verse, as well as these two interpretations that use an analytical method, and both adhere to the tradition. In the tafsir al-Maraghi and tafsir Ibn Katsir, there was an agreement that Surat Al-Jumah, verse 1-5 has the important essential points about the values of Islamic education, meaning about belief education, education of worship, and moral education as for the difference, it means the tafsir Ibn Katsir because it was interpreted according to the tradition and the opinion, and it was in the tafsir al-Maraghi and tafsir Ibn Katsir. There is no difference from the values of Islamic education, because the difference is found only in the method of clarification, especially in mentioning the wisdom of the Messenger’s mission.